2017
DOI: 10.1155/2017/2138169
|View full text |Cite|
|
Sign up to set email alerts
|

The Treadmill Exercise Protects against Dopaminergic Neuron Loss and Brain Oxidative Stress in Parkinsonian Rats

Abstract: Parkinson's disease (PD), a progressive neurological pathology, presents motor and nonmotor impairments. The objectives were to support data on exercise benefits to PD. Male Wistar rats were distributed into sham-operated (SO) and 6-OHDA-lesioned, both groups without and with exercise. The animals were subjected to treadmill exercises (14 days), 24 h after the stereotaxic surgery and striatal 6-OHDA injection. Those from no-exercise groups stayed on the treadmill for the same period and, afterwards, were subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 59 publications
2
30
0
Order By: Relevance
“…Moreover, in MPTP mice with 18 weeks of pretraining, Lau et al [126] showed protection of mitochondrial integrity and respiratory function in ST as compared to sedentary MPTP mice. In addition, da Costa group [133] also observed the drop in oxidative stress, which was measured as nitrite content and lipid peroxidation level.…”
Section: Study In Pd Animal Modelsmentioning
confidence: 95%
See 4 more Smart Citations
“…Moreover, in MPTP mice with 18 weeks of pretraining, Lau et al [126] showed protection of mitochondrial integrity and respiratory function in ST as compared to sedentary MPTP mice. In addition, da Costa group [133] also observed the drop in oxidative stress, which was measured as nitrite content and lipid peroxidation level.…”
Section: Study In Pd Animal Modelsmentioning
confidence: 95%
“…Moreover, physical exercise increased spontaneous locomotor activity and subthreshold L-DOPA-induced activity [133] and decreased depressive-like behavior, measured as immobility, in open field test [131]. Furthermore, physical training decreased contralateral bias in cylinder test [127] and ipsilateral rotations in amphetamine-induced rotational test [127,134] and reduced rotational asymmetry in apomorphine-induced rotational test [128,131,133]. Additionally, the use of BDNF receptor inhibitor K252a reversed the protective effect of exercise on rotational bias [128].…”
Section: Study In Pd Animal Modelsmentioning
confidence: 97%
See 3 more Smart Citations